2008
DOI: 10.1111/j.1872-034x.2007.00311.x
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsule technique protects hepatocytes from cryoinjury

Abstract: Our microencapsulation technique protects hepatocytes from cryoinjury. This novel technique could be utilized by hepatocyte banks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
3
13
0
Order By: Relevance
“…18,19,20 However, our current work provided no evidence for this. Indeed, ELS stored at -80°C showed progressive injury over the 12 months, which argues against any evidence for a major physical protection by encapsulation during storage at temperatures such as -80°C.…”
mentioning
confidence: 58%
“…18,19,20 However, our current work provided no evidence for this. Indeed, ELS stored at -80°C showed progressive injury over the 12 months, which argues against any evidence for a major physical protection by encapsulation during storage at temperatures such as -80°C.…”
mentioning
confidence: 58%
“…[7] reported the successful transplantation of cryopreserved tracheal allograft in a rabbit model. Other authors have reported the successful cryopreservation of hepatocytes [8,9] and whole murine and porcine livers [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Cryopreservation of cells microencapsulated in alginate has previously shown success in maintaining cell viability, stem cell characteristics, and cellular recovery [4245]. Cryopreservation allows for thorough testing of the encapsulated MSCs with the ability to thaw samples for validating cell viability, therapeutic protein concentration, sterility, and microbead integrity for ensuring that the highest-quality production has been performed.…”
Section: Introductionmentioning
confidence: 99%